Nordic and European Modernisms - Lothe, Jakob (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This e-book explores the growth and development of Nordic modernisms in a European context. Concentrating on and yet not limiting itself to the study of literary texts, the book shows that the emergence of modernism in the Nordic countries is linked to, and inspired by, the innovative works published in Western Europe and the USA towards the end of the nineteenth century and in the first decades of the twentieth century. Presenting Nordic art as multi-dimensional and dynamic, it also shows that, while responding to aspects of these innovative works, Nordic modernism itself contributed to modernism as a complex international trend. The plural form "modernisms" in the book's title indicates that the contributors adopt an understanding of modernism that, while recognizing the importance of the modernist movement between circa 1890 and 1940, is sufficiently elastic to include various forms of extension and continuation of Nordic modernisms in the post-war period. The book shows that the experience of crisis-cultural, political, moral, aesthetic-that underlies modernist artists' invention of radically new forms of expression was by no means limited to just one country or one identifiable group of writers; nor was it, as modernisms' global relevance makes clear, restricted to just one continent. At the level of historical reality, the First World War represents the culmination of a crisis which had its beginnings several decades earlier. The Second World War, along with the Holocaust, represents a second culmination of the crisis, and there is, this book suggests, a sense in which the experience of crisis has continued to influence and shape Nordic literature written in the post-war period. Over the first two decades of the twenty-first century, the experience of crisis has increasingly been extended to include a growing uncertainty about the future prompted by the reality of climate change.